2016
DOI: 10.2169/internalmedicine.55.6510
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Frame Rate Fluoroscopy on the X-ray Dose during Coronary Intervention

Abstract: Objective The aim of this study was to investigate whether the use of low frame rate fluoroscopy at 7.5 frames per second during coronary intervention could reduce radiation exposure in Japanese patients. Methods From December 10, 2014 to March 20, 2015, 84 consecutive patients with coronary artery disease who underwent coronary intervention in our institution were retrospectively collected and then divided into two groups: the LR group (fluoroscopy at 7.5 frames per second) and the OR group (fluoroscopy at 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…7 These findings replicate results of other studies investigating the efficacy of a frame rate reduction from 15 fps to 7.5 fps in reducing radiation dose. [8][9][10] In one retrospective cohort study, a conventional PCI protocol with 15 fps was compared with a protocol using 7.5 fps during fluoroscopic guidance and 10 fps during cineangiographic acquisition as well as selective fluoroscopic image storage. 8 That study found a significant reduction in total air kerma and total DAP in the radiation reduction protocol compared with the conventional protocol.…”
Section: Discussionmentioning
confidence: 99%
“…7 These findings replicate results of other studies investigating the efficacy of a frame rate reduction from 15 fps to 7.5 fps in reducing radiation dose. [8][9][10] In one retrospective cohort study, a conventional PCI protocol with 15 fps was compared with a protocol using 7.5 fps during fluoroscopic guidance and 10 fps during cineangiographic acquisition as well as selective fluoroscopic image storage. 8 That study found a significant reduction in total air kerma and total DAP in the radiation reduction protocol compared with the conventional protocol.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pyne et al [19] compared a standard dose cohort (15 f/s for fluoroscopy and cine angiography) and a reduced dose cohort (10 f/s for fluoroscopy and cine angiography), revealing that the reduced dose cohort exhibited a significant reduction in the mean total X-ray dose (1763.1 mGy vs. 1179.1 mGy; p<0.0001). In addition, Sadamatsu et al [20] described that a change in the frame rate from 15 f/s to 7.5 f/s for fluoroscopy could significantly reduce AK (701.4 ± 427.9 mGy vs. 936.8 ± 623.9 mGy; p=0.02). Moreover, Hansen et al [21] found that when the frame rate was decreased from 10 to 7.5 f/s during the PCI procedure, AK significantly reduced (703.0 vs. 621.0; p=0.041).…”
Section: Discussionmentioning
confidence: 99%